Transfection of Arctic Bryum sp. KMR5045 as a Model for Genetic Engineering of Cold-Tolerant Mosses - Byun, Mi Young; Seo, Suyeon; Lee, Jungeun; Yoo, Yo-Han; Lee, Hyoungseok (Frontiers in Plant Science, 2021)
Mosses number about 13,000 species and are an important resource for the study of the plant evolution that occurred during terrestrial colonization by plants. Recently, the physiological and metabolic characteristics that distinguish mosses from terrestrial plants have received attention. In the Arctic, in particular, mosses developed their own distinct physiological features to adapt to the harsh environment. However, little is known about the molecular mechanisms by which Arctic mosses survive in extreme environments due to the lack of basic knowledge and tools such as genome sequences and genetic transfection methods. In this study, we report the axenic cultivation and transfection of Arctic Bryum sp. KMR5045, as a model for bioengineering of Arctic mosses. We also found that the inherent low-temperature tolerance of KMR5045 permitted it to maintain slow growth even at 2°C, while the model moss species Physcomitrium patens failed to grow at all, implying that KMR5045 is suitable for studies of cold-tolerance mechanisms. To achieve genetic transfection of KMR5045, some steps of the existing protocol for P. patens were modified. First, protoplasts were isolated using 1% driselase solution. Second, the appropriate antibiotic was identified and its concentration was optimized for the selection of transfectants. Third, the cell regeneration period before transfer to selection medium was extended to 9 days. As a result, KMR5045 transfectants were successfully obtained and confirmed transfection by detection of intracellular Citrine fluorescence derived from expression of a pAct5:Citrine transgene construct. This is the first report regarding the establishment of a genetic transfection method for an Arctic moss species belonging to the Bryaceae. The results of this study will contribute to understanding the function of genes involved in environmental adaptation and to application for production of useful metabolites derived from stress-tolerant mosses.